TRENDS: Fridays of Revolution: Focal Days and Mass Protest in Egypt and Tunisia. (June 2020) - Ketchley, Neil; Barrie, Christopher
Focal days of protest are increasingly common to episodes of revolutionary mobilization. This paper explores the significance of focal days in patterning sustained protest in Egypt and Tunisia from 2011 to 2012. In Egypt, resource-poor activists exploited the confluence of worshippers on Fridays to mobilize mass transitory protest. This reliance on ritualized action hindered cross-sectoral coordination and meant mass protest often failed to inflict a direct economic cost. In Tunisia, there was no focal day of protest, in large part due to the coordinating hand of trade unions. In consequence, mass protest was more likely to span multiple sites, sectors, and tactics. These results suggest that oppositions can sustain mass mobilization even absent organizational capacity, but a reliance on a focal day limits the potential of protest over a political transition. Supplementary analyses point to the applicability of our findings to a number of other Arab Spring countries.